Analisis Kolaborasi Gaya Belajar dalam Penerapan Pembelajaran Berdiferensiasi Kelas X SMA Negeri 1 Singosari - Faruq, Junita Aliya; Melati, Freska Ela; Abadi, Machrus (Medan Resource Center, 2024)
This study analyzes the integration of learning styles in implementing differentiated learning for Grade X students at SMA Negeri 1 Singosari. Grounded in inclusive education principles, it emphasizes accommodating diverse learning styles identified by the VARK (Visual, Auditory, Reading/Writing, and Kinesthetic) model by Neil Fleming. Employing a descriptive qualitative method, the study involved 36 students and one Indonesian teacher, with data collected through observations, interviews, and questionnaires. Findings reveal that most students prefer visual and auditory learning styles, favoring visual media such as videos and concept map assignments. Differentiated learning implementation effectively addresses individual needs, enhancing engagement and academic outcomes. Furthermore, the study underscores the critical role of collaboration among teachers, parents, and the community in fostering an inclusive learning environment. These insights significantly contribute to understanding the application of learning style integration in Indonesian language education at the secondary school level.